Construction of a novel cuproptosis-related gene signature for predicting microenvironment, prognosis and therapeutic response in cervical cancer - Cui, Yaqi; Liu, Zihan; Zhang, Lingling; Men, Kang; Wang, Meng; Hu, Yingxin; Zhang, Zhiyuan; Liu, Xianbin; Wang, Xiao (Frontiers in Oncology, 2025)
IntroductionCervical cancer is a common malignant tumor in females, and its carcinogenesis needs further elucidation. Cuproptosis is a novel mode of cell death and its role in cervical cancer is largely unknown.MethodsThe data of 334 cases of cervical cancer patients were extracted from public databases, including TCGA, GEO, GSCA and Msigdb databases. The R package, Kaplan-Meier and Cox regression analysis were used to construct the prediction model. To confirm the validation of the model, FOXJ1 was over-expressed in HeLa and SiHa cells. CCK-8, EdU, colony formation and Transwell assays were used to test the proliferation, invasion and migration abilities. Western blotting was utilized to examine the changes of protein levels.ResultsWe constructed a six-gene signature based on cuproptosis-related genes (CRGs) using consensus clustering analysis which further classified the patients into Cluster A and Cluster B. Kaplan-Meier survival analysis revealed that the prognosis of patients with cervical cancer in Cluster B was significantly better than in Cluster A (p=0.027). By analyzing the differentially expressed genes (DEGs), we optimized the subclassification as high and low DEG score types, and revealed their differences in prognosis, copy number variation and single nucleotide variation. The scoring model showed effectiveness in distinguishing prognosis, tumor staging, immune microenvironment, immunotherapy and chemotherapy sensitivity. Moreover, the overexpression of FOXJ1 (one of the DEGs) significantly decreased the proliferation, invasion, migration and Epithelial-Mesenchymal Transition (EMT) process in cervical cancer cells. FOXJ1 promoted cuproptosis in cervical cancer cells, thereby inhibiting their proliferation, migration, and invasion capabilities.ConclusionOur study sheds light on the role of cuproptosis in carcinogenesis and is expected to facilitate the development of personalized treatment for cervical cancer.